Endoscopically inserted nasobiliary catheters for high dose-rate brachytherapy as part of neoadjuvant therapy for perihilar cholangiocarcinoma - Mukewar, Saurabh; Gupta, Arjun; Baron, Todd H; Gores, Gregory; Furutani, Keith; Haddock, Michael G.; Hallemeier, Christopher L. (Endoscopy, 2015)
Background and aim: Selected patients with unresectable perihilar cholangiocarcinoma can undergo neoadjuvant chemoradiotherapy followed by liver transplantation, which has been shown to improve survival. The aim of this study was to determine the feasibility and safety of endoscopic transpapillary insertion of nasobiliary tubes (NBTs) and brachytherapy catheters for high dose-rate (HDR) brachytherapy as part of this neoadjuvant chemoradiotherapy.Patients and methods: Medical records of patients undergoing biliary brachytherapy for hilar cholangiocarcinoma at the Mayo Clinic, Rochester were reviewed. Patients were treated with curative intent using external beam radiotherapy (4500 cGy), chemotherapy (5-FU or capecitabine), and HDR brachytherapy (930 – 1600 cGy in one to four fractions delivered over 1 – 2 days) prior to planned liver transplantation.Results: Between 2009 and 2013, 40 patients underwent biliary HDR brachytherapy via endoscopically placed NBTs (8.5 – 10 Fr). Patients had a median age of 55 years (range 28 – 68); 25 patients (62.5 %) had primary sclerosing cholangitis. Prior to therapy, 29 patients (72.5 %) had plastic stents, two (5 %) had metal stents, and nine (22.5 %) had no stents. Bilateral NBTs were placed in five patients (12.5 %). NBT/brachytherapy catheter displacement was seen in eight patients (20 %) – five intraprocedure and three post-procedure. A radiotherapy error and NBT kinking each occurred once. Post-procedure adverse events included: cholangitis (n = 5; 12.5 %), severe abdominal pain (n = 3; 7.5 %), duodenopathy (n = 3; 7.5 %), gastropathy (n = 3; 7.5 %), and both duodenopathy and gastropathy (n = 2; 5 %).Conclusion: HDR biliary brachytherapy administered via endoscopically placed NBTs and brachytherapy catheters is technically feasible and appears reasonably safe in selected patients with unresectable perihilar cholangiocarcinoma.